Deciphering the genetic programme triggering timely and spatially-regulated chitin deposition. - Moussian, B.; Letizia, A.; Martínez-Corrales, G.; Rotstein, B.; Casali, A.; Llimargas, M. (PLoS Genetics, 2015)
Organ and tissue formation requires a finely tuned temporal and spatial regulation of differentiation programmes. This is necessary to balance sufficient plasticity to undergo morphogenesis with the acquisition of the mature traits needed for physiological activity. Here we addressed this issue by analysing the deposition of the chitinous extracellular matrix of Drosophila, an essential element of the cuticle (skin) and respiratory system (tracheae) in this insect. Chitin deposition requires the activity of the chitin synthase Krotzkopf verkehrt (Kkv). Our data demonstrate that this process equally requires the activity of two other genes, namely expansion (exp) and rebuf (reb). We found that Exp and Reb have interchangeable functions, and in their absence no chitin is produced, in spite of the presence of Kkv. Conversely, when Kkv and Exp/Reb are co-expressed in the ectoderm, they promote chitin deposition, even in tissues normally devoid of this polysaccharide. Therefore, our results indicate that both functions are not only required but also sufficient to trigger chitin accumulation. We show that this mechanism is highly regulated in time and space, ensuring chitin accumulation in the correct tissues and developmental stages. Accordingly, we observed that unregulated chitin deposition disturbs morphogenesis, thus highlighting the need for tight regulation of this process. In summary, here we identify the genetic programme that triggers the timely and spatially regulated deposition of chitin and thus provide new insights into the extracellular matrix maturation required for physiological activity.